Memori Koleksi yang Terselesaikan: Praktik Seni Rupa Berkelanjutan sebagai Respons Kritis terhadap Obsesi Konsumerisme - Ananta Hari Noorsasetya (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
This study explores the influence of childhood memories, particularly the experience of "unresolved revenge" in the form of a failed tricycle ownership, on the process of creating works of art. This phenomenon is analyzed through the lens of psychoanalysis and consumerism criticism, where childhood fantasies transform into an obsession with collecting in adulthood, as an outlet for powerful passionate sensations. Qualitatively, works of art are positioned not only as manifestations of personal expression, but also as sustainable and critical practices. The articulation of art becomes a way to resolve consumerist trauma in a non-physical way, transforming the urge for unsustainable material accumulation (the infatuation of collecting) into artistic output that reflects and critiques the symbolic prestige value of commodities in the 1980s. This study concludes that personal memory-based art practices offer a sustainable framework for psychological recovery and social critique of the endless cycle of material desires.